2008
DOI: 10.4034/1519.0501.2008.0082.0005
|View full text |Cite
|
Sign up to set email alerts
|

Morbidade por Causas Externas em Idosos e sua Relação com Lesões Maxilofaciais

Abstract: RESUMO DESCRIPTORS DESCRITORESMorbidade; Idoso; Causas externas; Lesões maxilofaciais.Morbidity; Aged; External causes; Maxillofacial injuries. Morbidity of Elderly People by External Causes and its Relationship with Maxillofacial InjuriesObjective: To evaluate the morbidity due to external causes of elderly people and its relationship with maxillofacial injuries. Method: An observational, retrospective study was undertaken by the analysis of secondary data in a sample universe comprehending 8,671 files of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Advanced age leaves individuals more physically and mentally fragile, very often dependent and therefore more vulnerable, which further increases the significance of the trauma [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced age leaves individuals more physically and mentally fragile, very often dependent and therefore more vulnerable, which further increases the significance of the trauma [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the occurrence of trauma in the elderly have found high proportions of both younger elderly [13,20], and older elderly individuals [21,22] affected.…”
Section: Discussionmentioning
confidence: 99%